Psychiatric hospitalisation among individuals with intellectual disability referred to the START crisis intervention and prevention program. Issue 12 (26th August 2016) - Kalb, L. G.; Beasley, J.; Klein, A.; Hinton, J.; Charlot, L.
Abstract: Background: Little is known about inpatient psychiatric hospitalisation among adults with intellectual disability (ID) in the United States. Greater research is, therefore, required to inform efforts aimed at preventing this costly and restrictive form of care. Methods: Data were from 3299 individuals with ID (mean age = 31 years; SD = 14 years) who were referred to START (Systemic, Therapeutic, Assessment, Resources, and Treatment), a community‐based crisis intervention and prevention programme. A random effects logistic regression model was used to examine the association between 11 factors and caregiver report of psychiatric hospitalisation in the past 12 months. Results: Twenty eight percent of the sample had at least one psychiatric inpatient stay in the prior year. Factors associated with an increased likelihood of prior hospitalisation included: younger age, diagnosis of a psychotic disorder, a score of> 30 on the irritability subscale of the Aberrant Behavior Checklist, increasing number of psychiatric diagnoses, less severe ID, Black/AA race and not having a home and community waiver. Conclusions: Among this high‐risk referred group, more than 1 in 4 individuals were hospitalised in the year prior to referral. While results from the analyses will help profile those at risk for hospitalisation, the findings suggest that interventions at the policy level may play an important role in reducing psychiatric hospitalisation.